2019
DOI: 10.1111/jam.14340
|View full text |Cite
|
Sign up to set email alerts
|

Rahnella spp. are commonly isolated from onion ( Allium cepa ) bulbs and are weakly pathogenic

Abstract: Aims: Bacterial decays of onion bulbs have serious economic consequences for growers, but the aetiologies of these diseases are often unclear. We aimed to determine the role of Rahnella, which we commonly isolated from bulbs in the United States and Norway, in onion disease. Methods and Results: Isolated bacteria were identified by sequencing of housekeeping genes and/or fatty acid methyl ester analysis. A subset of Rahnella spp. strains was also assessed by multilocus sequence analysis (MLSA); most onion stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…A study by Asselin et al . [13] indicated the existence of several potential novel Rahnella species, isolated over a number of years from onion bulbs with signs of bacterial decay in the United States and Norway, and from creek water in the United States. Multilocus sequence analysis (MLSA) of a selection of onion isolates placed them in four separate clusters without reference strains in the genus Rahnella , suggesting they belong to four novel taxa [13].…”
Section: Full-textmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Asselin et al . [13] indicated the existence of several potential novel Rahnella species, isolated over a number of years from onion bulbs with signs of bacterial decay in the United States and Norway, and from creek water in the United States. Multilocus sequence analysis (MLSA) of a selection of onion isolates placed them in four separate clusters without reference strains in the genus Rahnella , suggesting they belong to four novel taxa [13].…”
Section: Full-textmentioning
confidence: 99%
“…[13] indicated the existence of several potential novel Rahnella species, isolated over a number of years from onion bulbs with signs of bacterial decay in the United States and Norway, and from creek water in the United States. Multilocus sequence analysis (MLSA) of a selection of onion isolates placed them in four separate clusters without reference strains in the genus Rahnella , suggesting they belong to four novel taxa [13]. A further potential novel Rahnella taxon was identified in this study following gyrB gene sequencing of a strain previously isolated from a Quercus species displaying symptoms of acute oak decline (AOD) in the Netherlands.…”
Section: Full-textmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study indicate that the reduction of rotten onion bulbs might be a result of the reduced counts of R. aquatilis by the ozone treatment during the two months of storage. It was previously found that scale discoloration and shrinkage appear when R. aquatilis is present with other pathogens in onion bulbs [3]. About 30% of onion bulbs are reported to be rotten due to pathogen invasion, suggesting that synthetic fungicides, bio fungicides or other novel methods should be used to reduce postharvest loss of onion bulbs [29].…”
Section: Ozone Reduced the Degree Of Rotting Of The Onion Bulb With Less Color Change And Softeningmentioning
confidence: 99%
“…However, their decay often occurs due to postharvest pathogens and results in serious economic loss [2]. Some bacterial pathogens including Rahnella strains are able to cause disease symptoms such as discoloration and softening of the onion bulbs at 5 °C [3], and other pathogens including fungi cause severe disease such as black mold, blue mold and neck rot in onion bulbs [4]. To prevent these diseases during cold storage, the practical use of sulfur fumigation has been carried out in storage rooms [5].…”
Section: Introductionmentioning
confidence: 99%